Az Európai Unió területfejlesztési politikájának válasza a globális városrégiók gazdasági erőfölényére - Besze, Tamás (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The centres of the global economy are metropoles which play important roles not only locally but also in global view. These agglomerations have two faces: these are the engine of the global economic development but they also hold up the possibility of a well balanced spatial development. They abstract many opportunities and financial sources from smaller settlements and the countryside because their size and wide relationship network. Todays there are lots of question without any answers concerning city networks. One of them is the role of these cities in a well balanced, policentric spatial development. This paper aims to analyze the growing process of the metropoitan areas and to introduce the policentric aspects of the spatial development in some european countries in-cluding Hungary.